Analisis Proksimat Karbon Aktif Kulit Langsat - Annisa Nabila Rahma; Desy Kurniawati (Jurnal Periodic Jurusan Kimia UNP, 2022)
Activated carbon is made from various raw materials, one of which is langsat leather. One of the uses of langsat peel activated carbon is as an adsorbent. The langsat peel activated carbon is made by carbonization process at 400 °C in a furnace. Activated carbon that has been carbonized will be activated with 0.1 M HNO3 for 2 hours. Proximate analysis which includes water content, ash content, volatile matter content, bonding carbon content and iodine uptake. Overall, the proximate analysis of activated carbon from langsat peel has a value that meets the requirements of SNI No. 06-3730-1995. Keywords — langsat peels, activated carbon, activation